Human Chromosomes - Miller, Orlando J.; Therman, Eeva (Springer New York, 2001)
This is the fourth edition of an acclaimed introductory textbook on the structure and function of human chromosomes. The explosion of information on human genetic diseases has meant that there is a greater need than ever for students, practising physicians, laboratory technicians, and researchers to have a concise, up-to-date summary of the normal and abnormal behavior of chromosomes. This book continues to fulfill that need, and is strengthened by the complete revision of material on the molecular genetics of chromosomes and chromosomal defects